Abdominoplasty complications – what additional risks do postbariatric patients carry?. Issue 12 (December 2021) - Sirota, Max; Weiss, Aviad; Billig, Allan; Hassidim, Ayal; Zaga, Jonathan; Adler, Neta
Summary: Purpose: Particular trends of postoperative complications following abdominoplasty are seen when patients present with a history of bariatric surgery. This study aims to analyze the risk factors for complications following abdominoplasty among those who did and did not undergo prior bariatric weight loss surgery. Method: Data of 144 patients who underwent abdominoplasty at our institution between 2009 and 2015 were reviewed. Prevalence of existing comorbidities and incidences of postoperative complications were recorded, and statistical analysis was carried out to establish differences between our cohorts. Results: Of 144 patients, 49 patients had prior bariatric surgery and 95 patients did not undergo surgery. There was no statistically significant difference between the groups for the prevalence of diabetes mellitus, coronary artery disease, hypertension, and anemia, although differences did exist for hypothyroidism and smoking history ( p  = 0.04 and 0.037, respectively). Postbariatric patients had more comorbidities than nonbariatric patients ( p  = 0.024). Postoperatively, there was no statistically significant difference between the groups for incidences of hematoma, necrosis, active bleeding, and symptomatic decrease in Hb, although differences did exist for infection (OR = 13.12), seroma (OR = 9.07), prolonged healing (OR = 5.28), and abundant drain secretions (OR = 5.24). Male gender and prior bariatric surgery were associated with higher overall rates of postoperative complications. Conclusions: Our findings validate the results of prior studies that report a higher prevalence of underlying comorbidities and postoperative complications among postbariatric surgery patients undergoing abdominoplasty. Furthermore, prior bariatric surgery was found to be an independent risk factor for the presence of any (OR 4.78 and p  < 0.001) and major (OR 4.050 and p  = 0.018) complications after abdominoplasty.